Discrepant Fertility in Brazil: an analysis of women who have fewer children than desired (1996 and 2006) - de Carvalho, Angelita Alves; Wong, Laura L. R.; Miranda-Ribeiro, Paula (Revista Latinoamericana de Población, 2016)
Two distinct groups with respect to realization of reproductive preferences coexist in Brazil: women who have more children than they would like and women whose reproductive period result in fewer children than they thought ideal. There is discrepant fertility in both cases. This study aims to enhance knowledge about this phenomenon by analyzing the discrepant fertility according to socio-demographic variables, especially for women who have fewer children than they desire and thus have a negative discrepant fertility (ndf). This study uses data from the National Demographic and Health Surveys for Women and Children from 1996 and 2006. The results show an increasing trend in ndf associated with fewer children, higher educational attainment, older age at first childbirth, and less time available to achieve the ideal number of children.